De hausse aan boeken over de Tweede Wereldoorlog - Lak, Martijn (TSEG - The Low Countries Journal of Social and Economic History, 2020)
The deluge of books on the Second World WarSince it is impossible to discuss all recently published books, studies and articles about the Second World War, this review article to highlights a number of specific developments, and discusses new perspectives. The main topics are the increasing emphasis in historiography on phenomena such as mass violence and its causes, the nature of the Third Reich, and, above all, the Holocaust.